2017
DOI: 10.1159/000484453
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-194 Regulates Lipopolysaccharide-Induced Cell Viability by Inactivation of Nuclear Factor-κ B Pathway

Abstract: Abstract:The present study explored the functional role of microRNA (miR)-194 in lipopolysaccharide (LPS) induced lung cell injury, along with the underlying mechanisms and to reveal the potential role in infantile pneumonia. Human fibroblasts WI38 cells were transfected with miR-194 mimic or miR-194 inhibitor, and the transfection efficiency was confirmed by quantitative realtime polymerase chain reaction (qRT-PCR). Thereafter, the cells were treated with or without LPS, and then cell viability, cell apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
(32 reference statements)
1
7
0
1
Order By: Relevance
“…Prior findings have indicated that miR-194-5p regulates apoptosis and genes targeted by miR-194-5p are enriched in apoptotic and inflammatory cell pathways, such as MAPK (Wang et al, 2019). The overexpression of miR-194 has been shown to alleviate cellular apoptosis in LPS-induced ALI (Xie et al, 2017). Forkhead box P2 (FOXP2), a transcription factor, is involved in chromatin remodeling, which regulates the transcription of downstream genes (Bruce and Margolis, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Prior findings have indicated that miR-194-5p regulates apoptosis and genes targeted by miR-194-5p are enriched in apoptotic and inflammatory cell pathways, such as MAPK (Wang et al, 2019). The overexpression of miR-194 has been shown to alleviate cellular apoptosis in LPS-induced ALI (Xie et al, 2017). Forkhead box P2 (FOXP2), a transcription factor, is involved in chromatin remodeling, which regulates the transcription of downstream genes (Bruce and Margolis, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that miR-194 expression was markedly decreased in A549 alveolar epithelial cells following infection with influenza A virus (IAV), and miR-194 could suppress fibroblast growth factor 2 (FGF2) expression at the mRNA and protein levels 89 . Xie and colleagues suggested that miR-194 increases cell apoptosis by inhibiting the NF- κ B pathway in WI38 cells, and it may be used as a potential targeted therapy for the treatment of infantile pneumonia 90 . In this present study, miR-92-x had a sharp down-regulation, while miR-194-y was significantly up-regulated in the A. c. cerana midgut 10 dpi with N. ceranae .…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutics that target the NF-κB family can inhibit its translocation during inflammation in a process termed trans -repression and can protect against the condition of pulmonary and airway obstruction-associated inflammation ( 23 , 39 ). Several studies have described the therapeutic implications on lung diseases and its pathogenesis by inhibiting the NF-κB pathway through microRNA-194 in infantile pneumonia ( 42 ), and curcumin and resveratrol combination in MRC-5 cells for idiopathic pulmonary fibrosis ( 28 ). The suppression of NF-κB in inflammatory diseases by natural compounds derived from plants have been reported for inflammatory diseases by inhibiting its downstream targets viz., and inflammatory mediators iNOS, COX-2 and PGE2 ( 43 - 47 ).…”
Section: Discussionmentioning
confidence: 99%